Characteristics of drift eliminators of an evaporative condenser - Singh, A. K.; Mohiuddin, A. K. M.; Kant, Keshav (Regional Centre for Energy, Heat and Mass Transfer - for Asia and the Pacific, 1993)
This paper deals with an experimental study of drift eliminators used in evaporative condensers to determine the pressure drop across them, drift loss and their effects on a refrigeration system performance using an evaporative condenser as one of its components. the experiments were conducted with single and double stages of both wooden drift eliminators (WDE) and concrete drift eliminators (CDE)using both forced and induced draft (ID). The orientation of the drift eliminator plates was varied from 15 degree to 90 degree with horizontal for a single fan speed. Based on the cost analysis for the variation of the pressure drop and the drift loss, an optimum angle of inclination of the drift eliminator plates is suggested. The COP of the refrigeration system increased with increase in fan speed and angle of inclination and decreased with increase in the number of stages. The use of forced draft resulted in better performance of the refrigeration system than with induced draft.